Vernacularization In The Sasak Language Translation Of The Qur'an (A Study Of Juz ‘Amma Al-Majidi) - Ahmad Askar (International Journal of Sociology of Religion, 2023)
Sasak Language Translation of the Al-Qur'an (Juz 'Amma al-Majidi) is a translation of the Al-Qur'an which aims to combine and connect the Al-Qur'an with cultural elements of the Sasak people that have been developed and inherited. hereditary. The method used is literature analysis using a historical approach. Thus, this research produced three findings, namely: 1) The form of vernacularization found in the Sasak Language Translation of the Al-Qur'an is the mention of God with the term "Grandma". 2) The use of the name God or Allah as "Grandma" cannot be separated from the beliefs of the Lombok people which have been passed down from generation to generation. Even after the Sasak people became familiar with Islam, they still called Allah SWT "Grandma kaji sak kuase". 3) Sasak is a language that has many dialects, so speakers of different dialects may not understand each other. Therefore, by prioritizing the vernacularization aspect in the Al-Qur'an, the Sasak language translation can not only be understood by some Sasak people, but also by all Sasak people, even though they have different dialects. From the results of this research, it can be proven that every translation of the Al-Qur'an that integrates and connects the Al-Qur'an with local cultural elements cannot be separated from the vernacularization aspect.